SORPTION POTENTIAL OF PENICILLIUM JANTHINELLUM FOR REMOVAL OF Cu(II) FROM ELECTROPLATING INDUSTRIAL EFFLUENT - ROUT CHADETRIK; SAZA RADHI NAIF; VIKAS BENIWAL (International Journal of Pharma and Bio Sciences, 2013)
To study the extent of removal of Cu(II) ions from the electroplating industrial effluent, metal resistant fungal strain of Penicillium janthinellum was selected for the present study. Response surface methodology was used to optimize the sorption process variables i.e. temperature (20-40 ºC), biomass concentration (0.5-2.5 mg/l), pH (2.0-6.0) and initial concentration of metal ions (20-100 mg/l). The maximum removal 59.48% of Cu (II) ions was observed at temperature 33.7 °C, biomass concentration 1.65 g/L, pH 5.88, and metal ions concentration 60.12 mg/L. Experimental results shows that sorption of Cu (II) ions by P. janthinellum indicates good biosorbent for removal of heavy metals from aqueous solution. However, the Cu(II) ions removal efficiency by P. janthinellum in electroplating industrial effluent was found to be 35â„….